Answer:
[tex] \dfrac{1}{2} \pm \dfrac{\sqrt{21}}{6} [/tex]
Step-by-step explanation:
[tex] 6x^2 - 6x - 2 = 0 [/tex]
Divide both sides by 2.
[tex] 3x^2 - 3x - 1 = 0 [/tex]
We compare it to the standard form:
[tex] ax^2 + bx + c = 0 [/tex]
We have a = 3, b = -3, c = -1.
To factor, we need two numbers that multiply to ac and add to b.
ac = 3 * (-1) = -3
-3 = -3 * 1; -3 + 1 = -2
-3 = -1 * 3; -1 + 3 = 2
There are no two integers whose product is -3 and whose sum is -3, so we cannot factor the trinomial. We use the quadratic formula to solve the equation.
[tex] x = \dfrac{-b \pm \sqrt{b^2 - 4ac}}{2a} [/tex]
[tex] x = \dfrac{-(-3) \pm \sqrt{(-3)^2 - 4(3)(-1)}}{2(3)} [/tex]
[tex] x = \dfrac{3 \pm \sqrt{9 + 12}}{6} [/tex]
[tex] x = \dfrac{3 \pm \sqrt{21}}{6} [/tex]
[tex] x = \dfrac{1}{2} \pm \dfrac{\sqrt{21}}{6} [/tex]